Tuning the selectivity of NH3 oxidation via cooperative electronic interactions between platinum and copper sites - Lu Chen; Xuze Guan; Zhaofu Fei; Hiroyuki Asakura; Lun Zhang; Zhipeng Wang; Xinlian Su; Zhangyi Yao; Luke L. Keenan; Shusaku Hayama; Matthijs A. van Spronsen; Burcu Karagoz; et al. (Nature Communications)
Abstract Selective catalytic oxidation (SCO) of NH3 to N2 is one of the most effective methods used to eliminate NH3 emissions. However, achieving high conversion over a wide operating temperature range while avoiding over-oxidation to NOx remains a significant challenge. Here, we report a bi-metallic surficial catalyst (PtSCuO/Al2O3) with improved Pt atom efficiency that overcomes the limitations of current catalysts. It achieves full NH3 conversion at 250 °C with a weight hourly space velocity of 600 ml NH3·h−1·g−1, which is 50 °C lower than commercial Pt/Al2O3, and maintains high N2 selectivity through a wide temperature window. Operando XAFS studies reveal that the surface Pt atoms in PtSCuO/Al2O3 enhance the redox properties of the Cu species, thus accelerating the Cu2+ reduction rate and improving the rate of the NH3-SCO reaction. Moreover, a synergistic effect between Pt and Cu sites in PtSCuO/Al2O3 contributes to the high selectivity by facilitating internal selective catalytic reduction.